Costs of Crohn's Disease According to Severity States in France: A Prospective Observational Study and Statistical Modeling over 10 Years. Issue 12 (December 2016) - Boschetti, Gilles; Nancey, Stephane; Daniel, Fady; Pariente, Benjamin; Lerebours, Eric; Duclos, Bernard; Bourreille, Arnaud; Cadiot, Guillaume; Fumery, Mathurin; Moreau, Jacques; Marteau, Philippe; Bouhnik, Yoram; et al.
Abstract : Background: To describe the medico–economic characteristics of Crohn's disease (CD), we implemented a multicenter study in France. Methods: From 2004 to 2006, disease severity states, direct (hospital and extra hospital) and indirect costs were prospectively collected over 1 year in patients with CD naive from anti–tumor necrosis factor alpha (infliximab) at inclusion. Economic valorization was performed from the French Social Insurance perspective, and a statistical modeling over 10 years was performed. Results: In 341 patients, the mean total costs of management were [Euro sign]6024 per year ([Euro sign]4675 for direct costs). As compared to patients in remission, costs were 4 to 6 times higher in patients in an active period and 19 times higher for patients requiring surgery (SURG). The most important expense items were medical and surgical hospitalizations (56% of total costs), including cost of infliximab (36% of hospitalization costs, i.e., 20% of total costs), indirect costs (22%), and drugs (11%). The statistical modeling over 10 years showed that most of the clinical course was spent in drug-responsive state (54%) with 26% of costs or in remission (32%) with 11% of costs; time spent in a SURG state was small (3.2%) but generated 48% of total costs. Conclusions: Before the introduction of self-injectable anti–tumor necrosis factor alpha, the most important expenses were supported by hospitalizations, explaining why the most costly states were for patients requiring SURG or dependent on inhospital administrated drugs. Projected data show that most time is spent in a stabilized state with appropriate treatments or in remission, and that costs associated with SURG are high. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 8 November 2016.